Realitas Kehidupan Islami dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar (Kajian Mimetik) - Zulfatun Anisah (Postgraduate Program Magister Pendidikan Agama Islam, 2018)
The value of Islamic education is occupied in everyday life, depicted also in literary works. One of them is the novel